Society for Maternal‐Fetal Medicine Special Statement: Tools for patient safety and quality case review and response: Obstetric sepsis - Society for Maternal‐Fetal Medicine (SMFM) (Pregnancy, 2025)
Abstract Sepsis‐related obstetric morbidity has significant consequences and can be a precursor to maternal mortality. Diagnosing and managing obstetric sepsis is uniquely challenging but a critical target for improving maternal outcomes. This document provides considerations and tools for breaking down a case of obstetric sepsis at the clinical unit level. In addition, this document outlines special issues with performing quality improvement projects as they relate to obstetric sepsis: (1) encouraging frontline implementers to consider the wide array of stakeholders involved in sepsis cases, (2) how to harness the electronic health record for enhancing care delivery, (3) challenges around common sepsis‐related metrics, (4) considerations around locations and transitions in obstetric sepsis care, and (5) considerations for ensuring equity in sepsis‐related projects.